Isolating hydrogen in hexagonal boron nitride bubbles by a plasma treatment - He, Li; Wang, Huishan; Chen, Lingxiu; Wang, Xiujun; Xie, Hong; Jiang, Chengxin; Li, Chen; Elibol, Kenan; Meyer, Jannik; Watanabe, Kenji; Taniguchi, Takashi; Wu, Zhangting; et al. (Nature communications, 2019)
Atomically thin hexagonal boron nitride ( h -BN) is often regarded as an elastic film that is impermeable to gases. The high stabilities in thermal and chemical properties allow h -BN to serve as a gas barrier under extreme conditions. Here, we demonstrate the isolation of hydrogen in bubbles of h -BN via plasma treatment. Detailed characterizations reveal that the substrates do not show chemical change after treatment. The bubbles are found to withstand thermal treatment in air, even at 800 °C. Scanning transmission electron microscopy investigation shows that the h -BN multilayer has a unique aligned porous stacking nature, which is essential for the character of being transparent to atomic hydrogen but impermeable to hydrogen molecules. In addition, we successfully demonstrated the extraction of hydrogen gases from gaseous compounds or mixtures containing hydrogen element. The successful production of hydrogen bubbles on h -BN flakes has potential for further application in nano/micro-electromechanical systems and hydrogen storage. Hexagonal boron nitride (hBN) is a two-dimensional material with wide band gap and high thermal and chemical stability. Here the authors demonstrate the formation and trapping of hydrogen gas bubbles in hBN interlayers upon plasma treatment, promising for extracting and storing hydrogen.